(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The good capability of zinc-tolerant probiotic of Lactobacillus plantarum tolerating high concentrations of Zinc+2 and producing Zinc Oxide Nanoparticles highlights the unique characteristics of these bacteria as a natural microbial cell nano-factory for a more efficient and environmentally friendly process of biosynthesis of these nanoparticles. The morphological and structural properties of Zinc Oxide Nanoparticles were determined by X-ray diffraction, Atomic Force Microscope and Field Emission Scanning Electron Microscope showed that the synthesized nanoparticles were crystalline, moderately stable, roughly spherical, hexonal in shape and pure We examined the antibacterial activity of the Zinc Oxide Nanoparticles and Zinc Oxide Nanoparticles/ Poly-?- hydroxybutyrate bionanocomposite on some pathogenic bacteria .It is clear in this the study that Zinc Oxide Nanoparticles/Poly-?-hydroxybutyrate bionanocomposite has stronger inhibitory effect on pathogenic bacteria compared with Zinc Oxide Nanoparticles only because the bionanocomposites exhibited reduced water uptake and superior gas as well as vapour barrier properties and causes increasing damage of the pathogenic bacteria.